Traumatic brain injury education for adult patients and families: a scoping review. (19th September 2018) - Hart, Tessa; Driver, Simon; Sander, Angelle; Pappadis, Monique; Dams-O'Connor, Kristen; Bocage, Claire; Hinkens, Emma; Dahdah, Marie N.; Cai, Xinsheng
ABSTRACT: Traumatic brain injury (TBI) is increasingly viewed as a chronic condition, bringing long-term needs for patient and caregiver knowledge pertaining to symptom and problem management over time. In light of these needs, we performed a scoping review of the literature on brain injury education provided to adult patients and/ or family members affected by TBI. Objectives were to describe the types of educational interventions that have been developed; to review the effects of these interventions; and to determine gaps that might be filled by future research efforts. Of 88 articles meeting search criteria and subjected to data extraction, 34 concerned education about mild TBI and 54, moderate to severe TBI. Most mild TBI articles focused on education in the Emergency Room, while most moderate/ severe TBI education was directed toward family members/ caregivers and was frequently combined with other treatment components, making the effects of education difficult to discern. Only 1 article incorporated elements of self-management training (SMT), a model proved effective in other chronic health conditions. We recommend further exploration of SMT principles in long-term TBI care, as well as more precise definition of treatment components in all patient and family interventions, so that the specific effects of education and other treatment elements may be more readily evaluated.